Constructive controversy and guanxi relationships for disaster recovery. Issue 4 (14th August 2017) - Chen, Yi-Feng; Kang, Yi; Tjosvold, Dean
Abstract : Purpose: How can governments and survivors prepare for and manage natural disasters? Post-disaster reconstruction researchers advocate that community involvement is needed to help survivors recover effectively. This study aims to propose that cooperative goals between government officials and survivors develop guanxi relationships and constructive controversy wherein survivors voice their opinions to aid disaster recovery. Design/methodology/approach: The authors adopted the critical incident technique (CIT), which has proved especially useful for studying complex issues, as well as site-intensive research for interviews and participant observation. After developing a local reputation and rapport by working in a residential resettlement area for two months, an author used the CIT to ask 118 survivors of the 2008 Sichuan earthquake to describe specific incidents when they interacted with government officials about recovery issues and then to rate survey items that measure independent and dependent variables. Findings: Results, including structural equation analyses, support the reasoning that cooperative goals between government and survivors facilitate guanxi and constructive controversy, which in turn produced effective disaster recovery, as indicated by survivors' social support, satisfaction, reduced stress and beliefs that government officials led effectively. Research limitations/implications: The data are self-reported and subject to biases and may not be accurate. Practical implications: In addition to developing theoretical understanding, the results can have important practical implications for strengthening relationships and constructive controversy between government and survivors. Social implications: Results suggest that communities have practical ways to prepare for disasters. Structuring cooperative goals among survivors, encouraging guanxi relationships, and training in constructive controversy should promote effective recovery from natural disasters. Originality/value: The paper develops theory and research on how leaders can promote community involvement for effective disaster management. The paper proposes that high-quality interpersonal relationships, also referred to guanxi, and the open-minded discussion of opposing ideas, labeled constructive controversy, are major components of effective community involvement. The paper adds to the literature by empirically documenting the utility of the Western-developed theory of cooperation and competition and the concept of constructive controversy for understanding the effectiveness of government leadership for disaster recovery in China.